2015
DOI: 10.1177/0885328215568984
|View full text |Cite
|
Sign up to set email alerts
|

A new method for meniscus repair using type I collagen scaffold and infrapatellar fat pad

Abstract: This new method for meniscal repair by combinative transplantation with type I collagen scaffold and infrapatellar fat pad showed meniscal regeneration and potential for suppressing inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 37 publications
1
31
0
1
Order By: Relevance
“…The increased expression of Ki67 marker in UCM treated cells compared to control, clearly indicates that supplementation of UCM to DMEM significantly influence meniscal cell proliferation. Similar increase in Ki67 positive expression was reported in meniscus cells grown in collagen type I scaffold along with infrapatellar fat pad (Oda et al 2015). CD34 marker expression was found to be absent in both the control and UCM supplemented meniscal cells indicating that the UCM does not induce any differentiation during the proliferation.…”
Section: Discussionsupporting
confidence: 79%
“…The increased expression of Ki67 marker in UCM treated cells compared to control, clearly indicates that supplementation of UCM to DMEM significantly influence meniscal cell proliferation. Similar increase in Ki67 positive expression was reported in meniscus cells grown in collagen type I scaffold along with infrapatellar fat pad (Oda et al 2015). CD34 marker expression was found to be absent in both the control and UCM supplemented meniscal cells indicating that the UCM does not induce any differentiation during the proliferation.…”
Section: Discussionsupporting
confidence: 79%
“…In this study, a full thickness cylindrical meniscal defect was used to evaluate scaffold performance. This defect type has been previously described in small animal models [11,26] and is optimal to ensure that the scaffold remains in situ during the experimental period. Previous studies using partial meniscectomy models have reported scaffold loss as a significant impact on the analysis of results [4] .…”
Section: Discussionmentioning
confidence: 99%
“…Radial-longitudinal tears [173] Electro spun type I collagen scaffolds and vascular/avascular region meniscal cells Avascular meniscal tears [174] Radio opaque electro spun scaffold Meniscal regrowth [176] Wrapping of meniscal defects with collagen membrane and injection of MSCs Tears in avascular zone [156] Aligned electro spun nano fibrous scaffold Radial tear [178] Collagen gel scaffold or HA hydrogel delivery of meniscal, synovial and adipose cells Bucket handle tear [177] Type I collagen scaffold/ infrapatellar fat pad Anterior 2 mm round holes [179] Chondrocyte + PLGA mesh scaffold + PRP Chondrocytes evaluated [180] Meniscal cells in fibre reinforced collagen-GAG scaffold + PRP Gene profiling study [168]…”
Section: Scaffolds Lesion and Study Type Referencesmentioning
confidence: 99%
“…Collagen gel scaffolds containing meniscal, synovial and adipose stem cells have been employed for meniscal repair [177] or in electrospun nanofibrous scaffolds [178]. The use of a type I collagen scaffold and infrapatellar fat pad for meniscal repair has been evaluated in rabbits [179]. PLGA mesh and fibre reinforced collagen-GAG scaffolds seeded with chondrocytes [180] or meniscal cells [168] supplemented with PRP have been evaluated for meniscal repair.…”
Section: Bioscaffolds Bioactive Substances and Bioadhesives And Menimentioning
confidence: 99%